Association Between Serum C-Reactive Protein Concentration and Nutritional Status of Malignant Tumor Patients - Yu, Jia Mi; Yang, Mei; Xu, Hong Xia; Li, Wei; Fu, Zhen Ming; Lin, Yuan; Shi, Ying Ying; Song, Chun Hua; Shi, Han Ping; Guo, Zeng Qing (Nutrition and cancer, 2019)
Background: The level of the systemic inflammatory marker C-reactive protein (CRP) is elevated in many patients with malignant disease and may be related to nutritional status. Objective: To analyze the association between serum CRP levels in patients with malignant tumors and their nutritional status. Method: A total of 3,692 cases were analyzed and the serum CRP levels were determined using an immunometric assay. Nutritional status was assessed by using patient-generated subjective global assessment (PG-SGA). The biochemical evaluation of prealbumin (PA), albumin (ALB), cholesterol (CHOL), and triglycerides (TG) were assayed within 48 h admission to the hospital. The association between serum CRP concentration and the nutritional status, the stage of the tumor and other factors was analyzed by univariate and multivariate logistic regression analysis. Result: Elevated serum CRP was observed in 47.6% (1,548/3,269) of patients compared with the reference value, and the median CRP concentration was 18.29 mg/l. Patient serum CRP concentrations in the malnourished group (PG-SGA B + C) were higher than in the well-nourished (PG-SGA A) patients (P < 0.05). The serum CRP level was related to the patients' age, gender, tumor stage, and was affected by hepatitis, liver cirrhosis, diabetes, but it has no effect on hypertension. The CRP high patients had lower PA and ALB levels, lower Karnofsky performance status scores, and higher PG-SGA scores (P < 0.05), and there was no relationship with CHOL and TG levels. Weight loss in the previous 1 mo was seen with CRP positive patients (P < 0.05). Conclusion: Almost 50% of malignant tumor patients had elevated serum CRP levels indicating a systemic inflammatory state. The nutritional status was worse in cancer patients with higher concentrations of serum CRP. The level of CRP was associated with the tumor stage, and, as stage is a prognostic factor, so can CRP be used as a prognostic maker in malignant tumors patients.